The Role of Zombie Firms in Industrial Sustainable Development: Evidence From Yangtze River Delta Urban Agglomerations - Wang, Haijing; Kong, Yusheng; Shi, Junguo (Frontiers in Environmental Science, 2022)
The development of the regional economy is of major concern against the backdrop of the ‘new normal’. As a problem that has persisted in China for decades, zombie firms have a negative impact on regional and industrial sustainable development. This study first presents a novel method for identifying zombie firms and then analyzes the characteristics of zombie firms in the Yangtze River Delta Urban Agglomerations during a specified period. A fixed-effect model is used to examine the impact of firm zombification on normal enterprise investment. Despite the low level of zombification of industrial enterprises in the Yangtze River Delta Urban Agglomeration, the results of the study indicate that it has a considerable negative influence on enterprise investment. After applying multiple methods for robustness testing and constructing instrumental variables to solve the endogeneity problem, our results have remained stable. The carbon intensity effect and the competitive weakening effect are also examined as two impact mechanisms. Our findings have significant theoretical and practical ramifications : (1) It introduces a novel concept for defining zombie firms, which will aid in the improvement of the technique of identifying zombie firms based on the Chinese Industrial Enterprise Database; (2) It proposes a novel approach to zombie firm research, and it is critical to better understand the harmful effects of zombie firms on industrial sustainable development and to make specific efforts to address them; (3) It makes recommendations to the government on how to establish industrial policy. The policy tilt towards state-owned enterprises should be adjusted, while regional economic characteristics should be fully considered to ensure the sustainable development of the industry and the region.